Polish-Ukrainian relations before and at the beginning of World War II in the light of the selected prose Borderland = Stosunki polsko-ukraińskie przed i na początku II wojny światowej w świetle wybranej prozy kresowej - Pomarańska, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to show the Polish-Ukrainian relations before and at the beginning of World War II in the light of the selected borderland prose. The study shows that the relationship between the two nations was complicated in terms of socio-political process in the period before and at the beginning of World War II. Those relations, despite the alleged harmony and concord in the prewar period of time turned into traumatic conflicts at the beginning of the war. The culmination of it was a genocide of Poles carried out by the Ukrainians in collaboration with the Soviets and the Germans.
Keywords: stosunki polsko-ukraińskie; proza kresowa; Polish-Ukrainian relations; borderland prose